EMBRYOGENESIS OF MYLOSSOMA DURIVENTRE (PACU-PEVA) - machado, Monica rodrigues ferreira (Ars Veterinaria, 2021)
This paper aimed to test a semi natural reproduction and to study the morphological development of the Mylossoma duriventre embryo until hatching. We selected six females with coelomic cavity bulging and softness and eighteen males that release sperm under light belly compression. We applied two doses of luteinizing hormone (0.0125 mg/kg and 0.125 mg/kg) for females and for males no hormonal induction was made, a semi natural reproduction was performed. After fertilization the embryos were transfer to a incubator and were evaluated every at 15-min intervals during the first hours of development and at one-hour intervals until hatching. The embryos are megalecites with meroblastic division, being visualized six different stages of development: fertilization, cleavage, blastula, gastrula, segmentation and pharyngula. In gastrulation (120-min post fertilization), there is formation of "tail bud" and appearance of somites during segmentation (510-min post fertilization), after the blastopore closure. The hatching occurred with 20 hours of development, at a temperature of 24°C. It was possible to reproduce the pacu peva in captivity, and the morphological development of the embryos showed some specificity when compared to other species and its results regarding embryonic development are essential for a better understanding of biology this species.